Influence of different plastic film packaging on the physiological and sensory quality of sweet oranges during cold and ambient storage - Alhassan, N; Abdulai, A; Mohammed , T (Journal of Postharvest Technology, 2022)
The effects of different plastic film packaging on physiological changes and sensory quality of sweet oranges were evaluated during a 9-week storage at 4⁰C or ambient (20±2⁰C). The oranges were seal-packaged with perforated polyphenylene films and biaxially-oriented polypropylene bags, and another group was shrink-wrapped in films, while another group served as the control. Oranges packaged with BOPP bags had the lowest weight loss at both cold storage (4⁰C) and ambient (20±2⁰C) compared to the other packaged and control fruits. However, the TA declined with an increase in TSS. Fruit sealed and packaged in plastic films preserved fruit firmness, taste, and flavor compared to the control fruit. However, the highest firmness (29.5N), taste score (9.0), and flavor acceptance (8.0) were observed with fruit sealed with BOPP bags at the end of storage. BOPP films greatly reduced fruit decay to 5%, relative to the control with 25% decay. However, the treatments should be evaluated for a wide range of citrus.